Essential budget / the children's submissions ; 2015 national budget counsultations launch report : the children's submissions - National Association of Youth Organisations (Zimbabwe) (Harare : National Association of Youth Organisations, 1966)
Children's views on the national budget making process.
Title from title screen.
System requirements: Adobe Reader.